Effect of Directors' Bonus Compensation, Institutional Ownership and Size of The Board of Directors on Profit Management - Wike Handayani; Agustin Fadjarenie (Publikasi Indonesia, 2023)
The current business development is very fast, which encourages organizations to be able to continue to present reliable and accountable financial information for their users. Reliable financial information is very necessary for decision-makers, especially stakeholders and potential investors, especially to make investments. Unqualified and reliable financial statements produce Earning Management and Financial Fraud Reporting. Research design is a blueprint, that is, a design for collecting, measuring, and analyzing data, which is designed to answer the formulation of problems. This study used a descriptive research design. This research is research with a quantitative approach. The purpose of this study is to analyze the influence between exogenous variables to endogenous variables, so this study is a type of Causal research. The type of quantitative research in this study is causal studies, which is a type of research based on the concept of cause. The conclusion of the results of this study is that CEO bonus compensation and the size of the board of directors have a positive effect on earnings management.